Photocatalytic degradation of humic acid using a novel photocatalyst: Ce-doped ZnO. Issue 1 (8th September 2016) - Birben, N. C.; Paganini, M. C.; Calza, P.; Bekbolet, M.
Abstract : This study aimed at investigating the photocatalytic degradation of humic acid (HA) as a representative of natural organic matter (NOM) by using Ce-doped ZnO as a novel material. Abstract : This study aimed at investigating the photocatalytic degradation of humic acid (HA) as a representative of natural organic matter (NOM) by using Ce-doped ZnO as a novel material. Following photocatalysis, HA degradation was characterized by specified UV-vis and fluorescence spectroscopic parameters as well as by the dissolved organic carbon (NPOC) content. Excitation–Emission Matrix (EEM) fluorescence features were also evaluated by using advanced techniques. Comparison of Ce-doped ZnO photocatalysis to TiO2 P-25 photocatalytic treatment of the HA samples was elucidated under similar experimental conditions. Kinetic modeling of the photocatalytic removal of HA expressed promising results indicating that Ce-doped ZnO could serve as an efficient catalyst for the degradation of NOM.